Myocardial deformation evaluated by two-dimensional echocardiography in lupic patients from a national hospital - Baltodano , Roberto (2020)
Background. Patients with systemic lupus erythematosus (SLE) are at high risk of cardiac compromise with high mortality. The subclinical diagnosis may improve their survival. Longitudinal myocardial deformation (strain) has been found to be useful in evaluating cardiac function in these patients. Objectives. Our aims were to evaluate myocardial function by analyzing the two-dimensional (2D) global longitudinal strain, to compare the longitudinal strain in SLE patients with controls, and to determine the correlation with SLE activity index. Material and Methods. 44 patients with SLE (50.0 ± 13 years) and 50 controls (49 ± 12 years) matched by age and sex, underwent transthoracic echocardiogram. Longitudinal strain was assessed using the speckle tracking method and SLE activity was estimated using the Systemic Lupus Erythematous Disease Activity Index (SLEDAI). A score of 4 or more, was defined as active SLE. Results. 2D global longitudinal strain was lower in patients with SLE than controls (- 17.3% ± 1.9% vs. -20%, ± 1.9% p = 0.00). The left ventricular ejection fraction (LVEF) had no specific differences in both groups in 2D (p = 0.650) or three-dimensional (3D) (p = 0.718). In lupus patients, SLEDAI ranged from 0 to 10, and 63.8% were inactive. Negative correlations were found between the SLEDAI score and 2D LVEF (Pearson's r = -0.372, p = 0.017); no correlations were found between the SLEDAI score and the 2D global longitudinal strain (Spearman's rho = - 0.091 p = 0.582). Conclusions: 2D global longitudinal strain was found to be decreased in the SLE group. This technique might can be a useful tool to assess cardiac function in these patiens.